2022
DOI: 10.1039/d2sm00688j
|View full text |Cite
|
Sign up to set email alerts
|

A double-network strategy for the tough tissue adhesion of hydrogels with long-term stability under physiological environment

Abstract: Achieving tough and stable tissue adhesion under physiological environment is of great significance for the clinical applications of hydrogel adhesives. The current tough hydrogel adhesives face the challenge in preservation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The DN strategy also allows hydrogels to covalently bond to tissues and endure large strains, preventing cohesive failures. [ 13 ] Although DN hydrogels are durable, mechanical damage may yet occur over the long term. Self‐healing hydrogels utilizing reversible cross‐linking networks have emerged as long‐lasting bioadhesives that can reconstruct damaged structures.…”
Section: Introductionmentioning
confidence: 99%
“…The DN strategy also allows hydrogels to covalently bond to tissues and endure large strains, preventing cohesive failures. [ 13 ] Although DN hydrogels are durable, mechanical damage may yet occur over the long term. Self‐healing hydrogels utilizing reversible cross‐linking networks have emerged as long‐lasting bioadhesives that can reconstruct damaged structures.…”
Section: Introductionmentioning
confidence: 99%
“…35 However, a high level of HS at wound sites may cause bleeding and the short therapeutic duration of HS requires multiple administrations; hence, slow and sustained administration of HS at wound sites is demanded for improved outcome. 21,36 In this research, we thus fabricated a novel HS-loaded hydrogel (i.e., P 338 /CMCS-heparin composite hydrogel (PCHgel)) consisting of P 338 , CMSC, and CaCl 2 . The physical properties and biosafety of PCHgel were assessed, and the tissue adhesion ameliorating ability was evaluated in detail using a rat abdominal and cecum tissue abrasion model 37 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that heparin sodium (HS) also displays excellent tissue adhesion blocking capability by inhibiting macrophage adhesion and aggregation at damaged sites . However, a high level of HS at wound sites may cause bleeding and the short therapeutic duration of HS requires multiple administrations; hence, slow and sustained administration of HS at wound sites is demanded for improved outcome. , …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, considering the use of hydrogels inside a human body in diverse biomedical applications, understanding the mechanical properties of completely swollen and equilibrated hydrogels in warm saline physiological conditions is important from the engineering perspective. [11,[26][27][28] Therefore, it is necessary to develop synthetic hydrogels with similar mechanical performance to soft, elastic, and tough bio-hydrogels that stably function under physiological conditions without performance deterioration while exhibiting deformation-rate independence.…”
Section: Introductionmentioning
confidence: 99%